Two new species of Gurania (Cucurbitaceae) from South America - Gomes-Costa, Géssica A.; Nee, Michael H.; Barbosa, Maria Regina De V. (Phytotaxa, 2015)
During the analysis of European and American herbaria collections for a taxonomic review of the Brazilian species of Gurania, two new South American species were found. Gurania jeffreyi occurs in Ecuador and Colombia and Gurania calathina is found only in Colombia. Descriptions and illustrations of the new species are presented with comments on affinities and differences between them and related species.